العلة النحوية عند المتقدمين والمتأخرين - RIZKI GUMILAR (Hasanuddin University, 2019)
الملخصتُعدّ العلة سمةً من أهم السمات في الفكر النحوي. فما من قاعدة نحوية إلا وقد علّلها النحاة، فكل حكم يُعلَّل، وكل ظاهرة نحوية لا بد لها من علة. فهذا ما جعل كثيرين من غير العرب يشهدون للعقلية العربية الفذّة، وجعل آخرين يتعجبون من وضع النحو العربي على ذلك الكامل.وقد جاء هذا البحث في خمسة أجزاء: تمهيد، وثلاثة مباحث، وخلاصة. المبحث الأول يتناول عن العلة ركن من أركان القياس النحوي، وهو يتكون من ثلاثة أجزاء: مفهوم القياس النحوي، وأنواع القياس، وأركان القياس. والمبحث الثاني يتناول عن مفهوم العلة النحوية ونشأتها وأقسامها، وهو يتكون من ثلاثة أجزاء: مفهوم العلة النحوية والتعليل، ونشأة العلة النحوية وتطورها، وأقسام العلة النحوية. والمبحث الثالث يتناول عن آراء المتقدمين والمتأخرين في العلة النحوية.الكلمات المفتاحية: التعليل النحوي، العلل النحوية، النحو العربي، أصول النحو ABSTRACTThe reason is one of the most important features of Arabic Grammatical. There is no grammatical rule unless the Scholars gives a reason for it. Every rule is given a reason, and every grammatical phenomenon must have a reason. This is what makes many non-Arabs bear witness to the unique Arabic mindset, and impress others with the status of perfect Arabic grammar.This research came in five parts: a preface, three sections, and a summary. The first section deals with the reason of the grammatical measurement, which consists of three parts: the concept of grammar measurement, types of measurement, and the pillars of measurement. The second section deals with the concept of grammatical reason and its origins and types. It consists of three parts: the concept of grammatical reason and reasoning, the emergence and development of grammatical reason, and the types of grammatical reason. The third section deals with the views of classical and contemporary scholars in the grammatical reason.Keywords: grammatical reasoning, grammatical reasoning, Arabic grammar, the origins of grammar.